Cookie monsters - Kendrick, Erika J. (Little, Brown and Company, 2023)
As twelve-year-old Brooklyn goes head-to-head against her rival to win her school's cookie-selling competition, her friends help her cope with the death of her mother and help her try to clinch the Cookie Queen title.